2019
DOI: 10.1542/peds.2018-3095
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss With Congenital Cytomegalovirus Infection

Abstract: OBJECTIVE:In this study, we determined the prevalence of hearing loss in 157 children with proven congenital cytomegalovirus (cCMV) infection. We looked at possible risk determinants for developing hearing loss and proposed recommendations for screening and follow-up in the newborn.METHODS: In a prospective 22-year study, 157 children with proven cCMV infection were evaluated for sensorineural hearing loss (SNHL). The development of SNHL was correlated with the type of maternal infection (primary versus nonpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 26 publications
1
100
2
9
Order By: Relevance
“…Most cCMV infections are asymptomatic and do not present a risk for the onset of late sequelae (5). Recent data demonstrated that primary maternal infections before the 14th week of pregnancy, the presence of a disseminated infection at birth, and imaging abnormalities in the neonate were risk factors for SNHL (52). This is a step toward the development of neonatal predictive markers that can be used to identify those at high risk of developing sequelae.…”
Section: Neonatal CMV Screeningmentioning
confidence: 99%
“…Most cCMV infections are asymptomatic and do not present a risk for the onset of late sequelae (5). Recent data demonstrated that primary maternal infections before the 14th week of pregnancy, the presence of a disseminated infection at birth, and imaging abnormalities in the neonate were risk factors for SNHL (52). This is a step toward the development of neonatal predictive markers that can be used to identify those at high risk of developing sequelae.…”
Section: Neonatal CMV Screeningmentioning
confidence: 99%
“…This hypothesis is supported by the existence of a difference in the mean age at first ABR between the two study groups, whereas AN infants underwent first ABR significantly earlier (p = 0.007) than not affected ones. In this light, also the distribution of AN cases along all trimesters of maternal infection (Table 1) suggests that a different pathogenesis is involved in these cases if compared to SNHL cases reported in medical literature, where a primary maternal infection of the first trimester of pregnancy is demonstrated to be a major risk factor [15,16].…”
Section: Discussionmentioning
confidence: 89%
“…Conflicting opinions exist about the influence of the type and timing of maternal CMV infection during pregnancy and the outcome in the child. Most studies stress the importance of primary maternal CMV infections, especially those occurring early in pregnancy, as having the greatest impact on the outcome of the newborn and child [7][8][9][10][11][12][13][14]. The relative contribution of maternal primary CMV infection during pregnancy to the risk of transmission to the fetus and newborn has been estimated at 40% (range 25 to 50%) for proven maternal primary CMV infections during pregnancy, and 1-2% for maternal non-primary or recurrent CMV infections during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of maternal primary CMV infection during pregnancy to the risk of transmission to the fetus and newborn has been estimated at 40% (range 25 to 50%) for proven maternal primary CMV infections during pregnancy, and 1-2% for maternal non-primary or recurrent CMV infections during pregnancy. In addition, primary maternal infections are more often associated with symptomatic congenital CMV infection, and long term sequelae, including hearing loss [7].…”
Section: Introductionmentioning
confidence: 99%